Eine Summe

Behauptung:

$$1\cdot 2^1+2\cdot 2^2+\ldots+n\cdot 2^n~=~\sum_{k=1}^n k\cdot 2^k~=~(n-1)\cdot 2^{n+1} + 2 \quad\quad(n\geq 1)$$



Beweis:

Induktionsanfang: n = 1

$$1\cdot 2^1 = 2 = 0 \cdot 2^2 + 2= (1-1)\cdot2^{1+1} + 2$$

Induktionsschritt: A(n) => A(n+1)

$$\begin{align*}\sum_{k=1}^{n+1} k\cdot 2^k &=~\sum_{k=1}^{n} k\cdot 2^k+ (n+1)\cdot 2^{n+1}\\ &\overset{\text{I.V.}}{=}~(n-1)\cdot 2^{n+1} +2+(n+1)\cdot2^{n+1}\\ &=~((n-1)\cdot 2^{n+1} +(n+1)\cdot2^{n+1}) +2\\ &=~(n-1+n+1)\cdot 2^{n+1} +2\\ &=~2n\cdot 2^{n+1} +2\\ &=~n\cdot 2^{n+2}+2\end{align*}$$

q.e.d.

Weiterlesen: Ein Produkt